Estimation of a quantile in finite population - Krapavickaitė, Danutė (Lietuvos matematikos rinkinys, 2002)
An estimator of the quantile of a study variable distribution function in finite population and its confidence interval is proposed. The estimator is adapted to the two-stage cluster sample which is used in a household budget survey carried out in Lithuania.